Development of Augmented Reality Learning Media Integrated with Experiential Learning to Enhance Students’ Chronological Thinking in High School History - Wiwi Fismariza; Ridho Bayu Yefterson; Azmi Fitrisia; Eka Asih Febriani (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aimed to develop and evaluate Augmented Reality (AR)-based learning media integrated with Experiential Learning Theory (ELT) to improve students’ chronological thinking skills. The study employed a Research and Development (R&D) method comprising needs analysis, design, development, expert validation, revision, and small- and large-group trials. The participants were Year 10 students (Phase E) at SMA Negeri 12 Padang. Data were collected through validation sheets, practicality questionnaires, and chronological thinking tests, then analysed using qualitative and quantitative descriptive techniques. The findings showed that the developed media met validity criteria based on assessments by subject-matter, media, and language experts, while also demonstrating high practicality for teachers and students. The media was also effective in improving students’ ability to sequence events, understand temporal relationships, and interpret historical timelines. Therefore, integrating AR with ELT offers an innovative approach to meaningful, experience-based history learning in classrooms.